Effect of the position of cyano group in α-cyano-functionalised diarylethene chiral fluorescent photoswitches on phototunable behaviours of cholesteric liquid crystals. Issue 9 (15th July 2021) - Qiao, Jinghui; Fan, Qingyan; Tian, Jiajun; Wang, Jingjing; Guo, Jinbao
ABSTRACT: Two novel chiral fluorescent photoswitches bearing unsymmetric α-cyanothienylethene as emissive/photosensitive scaffold and bridged binaphthyl moieties as chiral entities are synthesised. The effects of the position of cyano group in switch 8 and 9 on the photoluminescence and photoresponsive properties of them in organic solvent and cholesteric liquid crystals (Ch-LCs) are explored. Both of these two photoswitches undergo partial reversible Z/E photoisomerisation accompanied by changes in fluorescence intensity under the light irradiations in both organic solvent and LC media. However, fluorescence quantum yields of switch 8 are much higher than those of switch 9. Meanwhile, the initial helical twisting power (HTP) value of switch 8 in LC media is much higher than that of switch 9, which is ascribed to their distinct geometries arising from different positions of cyano group on the C=C bond in them. Moreover, the switch 8-doping Ch-LC system exhibits more fast response and better reversible switching behaviours compared to Ch-LC system containing switch 9. Finally, simultaneous photoswitching of the reflection colour and fluorescence intensity in the Ch-LC sample is demonstrated. This work provides an idea for designing chiral fluorescent photoswitches with advanced photoluminescence and photoswitching characteristics. GRAPHICAL ABSTRACT: uf0001